Brand Experience on Brand Love with Brand Credibility as a Mediator of Mobile Phones - Safitri, Ayu; Fajri, Annisa (Economics and Business International Conference Proceeding, 2024)
This study discusses Samsung mobile phone users or Android mobile phones among Gen-z at this time. The research method was carried out by collecting data through distributing questionnaires using g-form from Samsung mobile phone users in Semarang City. The testing tool for this study was Smart-PLS 4.1 or SEM-PLS. The results of the study showed that brand experience had a significant positive effect on brand love, brand experience had a significant positive effect on brand credibility, brand credibility had a significant positive effect on brand love, and brand credibility had a significant positive effect in mediating brand experience on brand love. These variables can be applied in order to increase user credibility on the brand.